Freeze frame : a photographic history of the Winter Olympics - Macy, Sue. (Washington, D.C. : National Geographic, 2006)
Highlights in the history of the Winter Olympics from their inception in 1924 to today, including profiles of the Olympic athletes and information on the lesser-known winter sports. Also includes an Olympic almanac with information about each Olympiad.
Includes bibliographical references (p. 92) and index.
Accelerated Reader/Renaissance Learning
A Junior Library Guild selection.
Keywords: Winter Olympics -- History -- Juvenile literature; Winter Olympics -- History -- Juvenile literature. -- Juvenile literature; Winter Olympics -- History; Winter Olympics -- History -- Pictorial works